Huntington S Disease Leads to Decrease of Gaba-A Tonic Subunits in the d2 Neostriatal Pathway and Their Relocalization into the Synaptic Cleft - Rojas-Montecinos, P (Academic Press, 2018)
GABA is a widely distributed inhibitory neurotransmitter. GABA-A receptors are hetero-pentameric channels assembled in multiple combinations from 19 available subunits; this diversity mediates phasic and tonic inhibitory synaptic potentials. Whereas GABA-A phasic receptors are located within the synaptic cleft, GABA-A tonic receptors are found peri- or extra-synaptically, where they are activated by diffusion of synaptic GABA release. In the neostriatum, GABA-A tonic subunits are present in the D2 medium-size spiny neurons. Since early impairment of these neurons is observed in Huntington s disease, we determined the ultrastructural localization of GABA-A-α5, -β3, -δ, -ρ2 and, for the first time, of GABA-A-ρ3 subunits, in the D2 pathway of the YAC128 murine model of Huntington s disease at various stages of disease progression. We report mislocalization of all five subunits from peri- and extra-synaptic spaces into the synaptic clefts of YAC128 mice, present in diseased mice as early as 6 months-old. The synaptic localization of GABA-A tonic receptors correlated with increased sensitivity to pharmacologic antagonists during extracellular electrophysiological recordings in neostriatal slices. Finally, the association of GABA-A tonic receptors with the D2 pathway in 6-month-old mice was largely lost at 12 months of age. © 2017 Elsevier Inc.